Maid a friend - Er, Xin Ni (2017)
Maid a Friend is a social campaign that aims to provide a fulfilling living and working environment for Foreign Domestic Workers (FDWs) in Singapore, such that they can continue to contribute to Singapore’s society sustainably. The campaign aimed to do this by promoting meaningful conversation between household members and their FDWs, through enhancing perceived behavioural control among the target audience. The target audience was household members between the ages 35 and 59, as this group had the poorest performance in the behaviour, yet are the ones who have the most involvement in the employment of FDWs. The campaign was successful in both encouraging meaningful conversation, as well as promoting friendship between the two parties. This paper details the key findings of our research that served as a guide to the campaign objectives, strategies and tactics. It is accompanied by an in-depth analysis of the post-campaign results, and evaluation of the campaign. Recommendations are also included to serve as a guide to future campaigns of a similar endeavour.